Guidelines for the preparation and submission of work schedule for construction project - Mohamad Zin, Rosli (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2008)
The lack of standardised guidelines for the preparation and submission of work schedule has contributed to several problems in construction project especially the extra efforts that have to be put in before parties involved in the project accept the work plan. This paper explores the current practice in project scheduling in the Malaysian construction industry and proposes guidelines that will alleviate the current problems in project scheduling. The methodology adopted was through interviews and questionnaire survey. The findings of the survey form a basis for the formulation of the guidelines. It consists of four main aspects of project scheduling which are process of acceptance of work schedule, responsibilities of the contracting parties, application of work schedule, and implications of work schedule. With the establishment of these guidelines a standardised approach for the preparation and submission of work schedule can be achieved thus will be able to minimise some of the problems that are currently hinder the full application of project scheduling in various construction projects. The proposed guidelines will pave the way for the inclusion of work schedule as part of the contract document.